2018
DOI: 10.1002/hbm.24356
|View full text |Cite
|
Sign up to set email alerts
|

Spatio–temporal patterns of cognitive control revealed with simultaneous electroencephalography and functional magnetic resonance imaging

Abstract: Optimal performance depends in part on the ability to inhibit the automatic processing of irrelevant information and also on the adjusting the level of control from one trial to the next. In this study, we investigated the spatio–temporal neural correlates of cognitive control using simultaneous functional magnetic resonance imaging and electroencephalography, while 22 participants (10 women) performed a numerical Stroop task. We investigated the spatial and temporal dynamic of the conflict adaptation effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 120 publications
(146 reference statements)
3
14
0
Order By: Relevance
“…While both switch and repeat trials modulated the connection from IFJ to ACC positively, the modulation was significantly stronger for switch trials. This supports previous studies associating signaling from IFJ to ACC with increased cognitive effort (Harding et al, 2015; Hinault et al, 2019). Importantly, this difference in cognitive modulation was exclusively found in the reward condition suggesting that distinct motivational settings differentially affect neural interactions between IFJ and ACC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While both switch and repeat trials modulated the connection from IFJ to ACC positively, the modulation was significantly stronger for switch trials. This supports previous studies associating signaling from IFJ to ACC with increased cognitive effort (Harding et al, 2015; Hinault et al, 2019). Importantly, this difference in cognitive modulation was exclusively found in the reward condition suggesting that distinct motivational settings differentially affect neural interactions between IFJ and ACC.…”
Section: Discussionsupporting
confidence: 91%
“…Third, the model space comprised all possible permutations of modulatory connections between the VOIs, except for the connection from IFJ to ACC. Since previous work on effective connectivity during cognitive tasks showed that the IFJ directs activity in the ACC (Harding et al, 2015; Hinault et al, 2019), the connection was operative in all models. This amounted to 32 models per family (see Supplementary Figure) and 96 models in total.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…This mediation was observed during both WM cue and problem verification phases, and involved synchronization between the IFG and occipital lobe regions. IFG activity has been reported when rule updating and maintenance is required 67,68,69,70 , and its coupling with the occipital lobe was previously observed with the same task in fMRI 16 , suggesting a major role for the interplay between rule updating and sensory processing. The present study shows that, in contrast with a disconnection account, there is no absolute interruption of network structure or communication, but rather reduced integrity leads to reduced synchrony between brain regions, and slower transitions for task-related modulations of that synchrony.…”
Section: Discussionmentioning
confidence: 66%
“…Investigations in young adults revealed distinct associations of alpha and gamma oscillatory variability with BOLD signal variability (e.g., Hinault et al, 2019b;Scheeringa & Fries, 2019) that could further our understanding of brain changes with age and pathology. Balster et al (2013) reported that simultaneous resting-state EEG and fMRI recording could be more sensitive to age-related changes than fMRI alone.…”
Section: M/eeg Informed Fmri Studiesmentioning
confidence: 99%